Family nursing care for a family with an adolescent in Aceh Besar Regency - Intan Putri Munawarah; Fithria Fithria (Indonesian Journal of Health Science, 2026)
The family plays a crucial role in maintaining and improving its members’ health, particularly during adolescence, a period characterized by vulnerability to various health behaviors and issues. However, several issues remain prevalent, including inadequate menstrual hygiene and handwashing practices, smoking behavior within the family, and suboptimal management of gastritis. These conditions highlight the importance of a family nursing approach to enhance family independence in managing health. This final scientific paper aimed to describe the process of family nursing care for a family with an adolescent experiencing health problems related to menstrual hygiene, handwashing practices, smoking behavior, and gastritis. Based on the assessment conducted from December 30, 2025 to January 1, 2026, in Gampong Lam Ujong, Darussalam Sub-district, Aceh Besar Regency, three priority nursing diagnoses were established collaboratively with the family: ineffective family health management related to menstrual hygiene and handwashing practices, risk-prone health behavior in the form of smoking, and ineffective health management related to gastritis. Interventions were developed based on the five family health tasks. Interventions for the first diagnosis focused on improving menstrual hygiene practices and the six-step handwashing technique. The second diagnosis focused on education regarding the dangers of smoking, teaching the Spiritual Emotional Freedom Technique (SEFT), and creating a smoke-free environment. The third diagnosis included health education on gastritis, promoting regular eating patterns, reducing consumption of instant foods, and applying deep-breathing relaxation techniques and warm compresses. Evaluation results indicated improvements in knowledge, changes in attitude, and the family’s ability to implement clean, healthy lifestyle behaviors, support smoking cessation efforts, and engage in more structured self-management of gastritis. Community health centers are expected to strengthen family-based education and support programs to promote sustained improvements in health status